If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 3) + -2 = 22 Reorder the terms: (3 + 7x) + -2 = 22 Remove parenthesis around (3 + 7x) 3 + 7x + -2 = 22 Reorder the terms: 3 + -2 + 7x = 22 Combine like terms: 3 + -2 = 1 1 + 7x = 22 Solving 1 + 7x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 7x = 22 + -1 Combine like terms: 1 + -1 = 0 0 + 7x = 22 + -1 7x = 22 + -1 Combine like terms: 22 + -1 = 21 7x = 21 Divide each side by '7'. x = 3 Simplifying x = 3
| 6k+24=3k-12 | | 12v^7w^9+16v^4w^5x^8=0 | | 11+5(k+1)=3k-(6k-6) | | F(x)=lhx+2 | | 4.2x-2.1=1.68-5.4x | | -26+3x=-36+6x | | 5-3x=7x+5 | | 102=5w+17 | | -9(x-4)=-3x+42 | | 12-2x=2x+8 | | X=8-3(-3) | | A=10x+y+2 | | 21+3x=56 | | -9x-4y=-4 | | -x=-3+2x | | 210p=1890 | | 3x-5=12+3x | | 6n+10=-4n+50 | | 8*n=32 | | 16x^2-27e=0 | | 10=6x+3 | | 9x+11=6x+-9+3 | | 3x-18=12+7x | | 4x-4x+5=12 | | 4+5(x-2)=6+7(x-2) | | (10-2x)(8-2x)(x)=f(x) | | -8+x=4x+1 | | cos+2sec=-3 | | -16=2(1-5x)+4 | | x+3.5=8.5-9x | | 10x-5(x-2)=30 | | 7-4x-3x-5=6x+1+2x-3 |